Intracoronary secretin increases cardiac perfusion and function in anaesthetized pigs through pathways involving β‐adrenoceptors and nitric oxide. Issue 5 (29th January 2013) - Grossini, Elena; Molinari, Claudio; Morsanuto, Vera; Mary, David A. S. G; Vacca, Giovanni
<x xml:space="preserve">Abstract</x> Secretin has been implicated in cardiovascular regulation through its specific receptors, as well as through β‐adrenoceptors and nitric oxide, although data on its direct effect on coronary blood flow and cardiac function have remained scarce. The present study aimed to determine the primary in vivo effect of secretin on cardiac function and perfusion and the mechanisms related to the autonomic nervous system, secretin receptors and NO. In addition, in coronary endothelial cells the intracellular pathways involved in the effects of secretin on NO release were also examined. In 30 pigs, intracoronary secretin infusion at 2.97 pg for each millilitre per minute of coronary blood flow at constant heart rate and aortic blood pressure increased coronary blood flow, maximal rate of change of left ventricular pressure, segmental shortening, cardiac output and coronary NO release (P < 0.05). These responses were graded in a further five pigs. Moreover, while blockade of muscarinic cholinoreceptors (n= 5) and of α‐adrenoceptors (n= 5) did not abolish the observed responses to secretin, blockade of β1‐adrenoceptors (n= 5) prevented the effects of secretin on cardiac function. In addition, blockade of β2‐adrenoceptors (n= 5) and NO synthase inhibition (n= 5) prevented the coronary response and the effect of secretin on NO release. All these effects were abolished by a secretin receptor inhibitor (n= 5). In coronary endothelial cells, the increased NO production caused by secretin was found to be related to cAMP/protein kinase A signalling activated as downstream effectors of stimulation of secretin receptors and β2‐adrenoceptors. In conclusion, in anaesthetized pigs secretin primarily increased cardiac function and perfusion through the involvement of specific receptors, β‐adrenoceptors and NO release.